2016
DOI: 10.1002/jbm.a.35869
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of two‐layer dissolving polymeric microneedle patches for insulin transdermal delivery in diabetic mice

Abstract: Dissolving microneedles (MNs) display high efficiency in delivering poorly permeable drugs and vaccines. Here, two-layer dissolving polymeric MN patches composed of gelatin and sodium carboxymethyl cellulose (CMC) were fabricated with a two-step casting and centrifuging process to localize the insulin in the needle and achieve efficient transdermal delivery of insulin. In vitro skin insertion capability was determined by staining with tissue-marking dye after insertion, and the real-time penetration depth was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…The operation parameters were followed as described in our previous study. 8 Skin penetration depths for different ratios of PVP MNs and the degree of skin repair were observed immediately without histological sections.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…The operation parameters were followed as described in our previous study. 8 Skin penetration depths for different ratios of PVP MNs and the degree of skin repair were observed immediately without histological sections.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The diabetic mice were induced as described in a previous study. 8 All animal experiments were approved by the Chang Gung University in accordance with the guidelines for animal experimentation (IACUC approval number: CGU15-044). Male BALB/c mice with an average weight of approximately 27 g (provided by the National Laboratory Animal Center, Taiwan) were injected with streptozocin (STZ, Sigma, USA) in 0.1 ml of a sodium citrate buffer (0.05 M, pH 4.5), 200 mg kg À1 .…”
Section: In Vivo Delivery Efficacy Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have shown that intradermal administration of specific drugs using microneedles increases the therapeutic efficacy compared to the intramuscular and the subcutaneous routes 5 . As reported previously, the dissolving microneedle patch can rapidly release the drug in skin; this is an efficient way to deliver large molecules like insulin 6 . Thus, microneedles provide easier route for transdermal drug delivery for molecules that are not readily absorbed topically.…”
Section: Introductionmentioning
confidence: 63%
“…In one research, Lee et al. used gelatin and sodium carboxymethyl cellulose to fabricate microneedles and illustrated a surefire result in releasing insulin . PassPort is an insulin patch, which is anticipated to enter to the market soon .…”
Section: Strategies To Improve Non‐invasive Insulin Therapymentioning
confidence: 99%